Directors' Liability and Optimization of Legal Protection for the Shareholder Loan Agreement Between PT ASDP Indonesia Ferry (Persero) and PT Indonesia Ferry Properti - Muhammad Fahrudin; Suherman Suherman; Atik Winanti (International Forum of Researchers and Lecturers, 2025)
This research aims to analyze the optimization of legal protection and risk mitigation for PT ASDP Indonesia Ferry (Persero) as the lender in a Shareholder Loan (SHL) Agreement with PT Indonesia Ferry Properti, and to examine the legal implications of the PT ASDP directors' liability in the SHL decision-making process. The research method employed is normative juridical with a literature study approach. The findings indicate that although the SHL execution has procedurally met legal principles and Good Corporate Governance (GCG), the optimization of legal protection for PT ASDP requires the enhancement of more proactive post-disbursement fund supervision clauses and, crucially, the implementation of specific collateral to mitigate credit risk, considering the current agreement is still reactive and lacks specific collateral. Furthermore, the directors of PT ASDP bear responsibilities under Article 97 of the Company Law and the principle of fiduciary duty. The Business Judgment Rule (BJR) doctrine can shield directors from personal liability if decisions are made in good faith, with due care, without conflicts of interest, and accompanied by risk mitigation efforts, wherein the implementation of GCG principles is fundamental. Violations may lead to civil, criminal, or administrative liability. This research concludes the importance of contractual strengthening of the SHL and strict adherence to GCG to protect company assets and directors.